Revision of the genus Stenogephyra Lyneborg (Diptera: Therevidae: Phycinae) - Webb, Donald W.; Hauser, Martin (Zootaxa, 2011)
The genus Stenogephyra Lyneborg is revised and includes seven species from the Afrotropical Region. Stenogephyra dianeae spec. nov., S. janiceae spec. nov., S. namibiensis spec. nov., S. parkeri spec. nov., and S. schlingeri spec. nov. are new to science. Each new species is described and illustrated and the pupa of S. torrida is described and figured. Distribution maps for each species are given. A key to the species of Stenogephyra is provided.